Analysis and simulation of z-source inverter control methods - Mohd Salfarulizaman, Kamarul Baharin (2012)
This thesis presents the analysis of switching control technique approach to Zsource inverter. Z-source inverter is a new inverter that can be implemented in all types of converter operation. This advantage has made the control methods became more complicated due to the Z-impedance and the different switching characteristics. The inverter model was constructed by using MATLAB/Simulink with the SimPowerSystems Block Set. The purposed of this project is to construct analysis and investigate the Zsource inverter and its switching techniques. i.e., constant boost and maximum boost PWM. These two types of switching techniques are analyzed and compared for each other. The Simple Boost control with independence relation between modulation index and shoot-through duty ratio is also simulated and analyzed. The selection of high modulation index and shoot-through duty ratio can reduce the inverter’s dc link voltage overshoot and increasing power delivery capacity of the inverter. The detail analysis and comparison of the switching control techniques are presented in this thesis.